ANALISIS PERMASALAHAN PENGELOLAAN SUNGAI DELI (PROBLEM ANALYSIS OF DELI RIVER MANAGEMENT) - Nobrya Husni (Inovasi, 2017)
Consideration of the historical value and the ecology condition of the Deli river to be a factor supporting the implementation of the management of the river Deli is adjusted to the development of Medan as the capital of the third largest province in Indonesia. This paper aims to: a) identify problems in the arrangement of the Deli river, and; B) provide input regarding the management of the Deli river. The scope of writing is the condition of chemistry, physics, and biology of the Deli river, the socio-cultural conditions of the community, as well as regulations that support the management of the Deli river. This paper is a literature review with data sources derived from literature such as journals, theses / dissertations, and legislation, as well as previous research on Deli rivers and rivers in other cities, both in Indonesia and the world that has been successful in river management. The data will be analyzed descriptively qualitative and then done comparison between river management in Medan city with other city in Indonesia / world. The problems faced today in the management of the Deli River today, can be categorized into 2 (two) problems, namely: a) the unavailability of the river management plan / model; And, b) unavailability of Local Regulation (Perda) on river management. Deli River is one of the rivers that belong to the Deli watershed, so the success of Deli River management is highly dependent on the management of the Deli watershed as a whole. Management of the Deli River can be done by adapting WFD conducted in Europe and SA conducted in the UK. In the planning stage of Deli River management, it is important to identify criteria to represent relevant aspects of sustainability objectives. The identification of these criteria is carried out by the Provincial / Regency / City Government in accordance with their authority. The involvement of the DAS Forum, academics, entrepreneurs and the community becomes an important factor for success in the identification process. Management of the Deli River must be holistic, from upstream to downstream. The involvement of governments, businesses, academics, practitioners, and communities is essential for sustainable management of the Deli River. Keywords: Deli river, Deli watershed, watershed management